Processing of nanostructured nickel-based magnetic materials - School of Materials Science and Engineering (2008)
A systematic investigation into the structure and properties of five commercially available nickel-based soft magnetic materials was carried out. The five systems are Fe23Ni77, Fei6Ni77Cu7, Fei6Ni77Cu5Cr2, Fei6Ni77Mo7 and Fei6Ni77Nb7. These alloy systems were processed by ball milling to obtain the compound with grain size of several tens of nanometers in length scale. Depending on the exact chemical composition, some amorphous or semi-amorphous phases were deposited at the inter-granular layers as evidenced from the TEM micrographs. As the grain size decreases to several tens of nanometer in scale, results of the ball milled powders showed that the all the five systems exhibited coercivities that increased with grain size, contrary to the random anisotropy model. These were attributed to the internal stress generated from the mechanical forces. Stress-annealed magnets sintered from the alloyed powders showed strong dependency of the anisotropy on grain size where the coercivity decreases with grain size. The effect of alloying elements on the magnetic properties of these nanostructured magnets suggest that it is less significant compared to the effect on grain size. Although the coercivity varies with the alloying elements, the critical factor on its behaviour is dominated by the grain / particle size.